#CroakeyGO: Walking as an act of journalism to engage not distance the public in health reporting. (30th September 2020) - Williams, M; Sweet, M; Armstrong, R; McInerney, M; Ward, M
Abstract: Health as it is reported in mainstream media is narrow and communities are often excluded, despite being where the experience of health occurs. A wide range of research indicates that it is through narratives of community members that media and health messages are best conveyed, and community members now have a range of platforms for quickly conveying information to each other and the media. However, there have been surprisingly few innovations for journalists to use this material, or to better connect with the public and report more accurately about health. Our experience across several journalism projects demonstrates how quickly and deeply health content can be developed in collaboration with communities. One example is #CroakeyGO - an innovation in public interest journalism that gathers, walks and talks with community members together at a defined time and location about health-related matters. #CroakeyGO brings together diverse voices from local communities - people who might otherwise not connect. This stimulates discussion about health issues beyond the individual, including system- and environmental-level issues that impact local lives. #CroakeyGO also means respecting Indigenous peoples' connection to Country on which we walk and reflecting on intergenerational inequities and solutions Indigenous knowledges offer. To date we have published more than 40 articles from #CroakeyGO events around metropolitan and regional Australia. We have collaboratively produced social media and other editorial content with community members and stimulated enduring networks for health planning, advocacy and research. #CroakeyGO reinforces that improving health in a community requires more than just additional services, and that transformations in journalism can facilitate and support rather than hinder collective action. Key messages: Innovations in journalism are required and possible to improve health reporting. Communities are willing to engage in health reporting.